Used betta fish multicolor as therapy for reducing addictive social media use in the covid-19 outbreak - Nilma Zola; Rima Pratiwi Fadli; Yola Eka Putri; Dominikus David Biondi Situmorang; Ifdil Ifdil (Universitas Negeri Padang, 2021)
During the COVID-19 pandemic, people used social media to communicate and entertain themselves. Yet, excessive social media use can cause anxiety and sadness. Hence, fresh social media addiction therapies are crucial. We suggest treating social media addiction with colorful Betta fish. This fish's brilliant colors and interesting behavior reduce stress and anxiety and promote well-being. Betta fish are low-maintenance pets that may be kept in a small tank at home or at work. Interacting with animals helps improve mental health. So, the